2019
DOI: 10.1186/s12875-019-1041-5
|View full text |Cite
|
Sign up to set email alerts
|

Standardized warfarin monitoring decreases adverse drug reactions

Abstract: BackgroundWhile warfarin is the most commonly prescribed medication to prevent thromboembolic disorders, the risk of adverse drug reactions (ADR) poses a serious concern. This prospective study evaluated how primary care providers (PCP) and cardiologists at our Institution managed patients treated with warfarin with the goal of decreasing the number of warfarin ADRs.MethodsA multidisciplinary anticoagulation task force was established at our Institution in 2014 to standardize warfarin monitoring and management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Explaining that their physicians used Warfarin in patients who had well self-management (Alalwan et al, 2017). HAS-BLED is scoring system to assess bleeding risk in patient with atrial fibrillations based on factors such as hypertension, abnormal renal and liver function, stroke, bleeding tendency, labile INR in patients taking warfarin, elderly age and the use of other medications (Shields et al, 2019). HAS-BLED has been found to predict hemorrhage risk better compared with another score (Hart et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explaining that their physicians used Warfarin in patients who had well self-management (Alalwan et al, 2017). HAS-BLED is scoring system to assess bleeding risk in patient with atrial fibrillations based on factors such as hypertension, abnormal renal and liver function, stroke, bleeding tendency, labile INR in patients taking warfarin, elderly age and the use of other medications (Shields et al, 2019). HAS-BLED has been found to predict hemorrhage risk better compared with another score (Hart et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating the prevalence of warfarin have been done and the results showed an overall decline in the prescribing rate of warfarin, a study showed that the usage of warfarin in atrial fibrillation decreased from 69.8% in 2008 to 42.2% in 2014 and another showed a significantly decrease from 72.2% to 42.1% over a 5-year period from 2013 to 2017 (Alalwan et al, 2017;Shields et al, 2019). However, in Saudi Arabia the extent to which the DOACs have been used is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, at least one pharmacogenomic variant in most patients was identified; however, relevant medication use was infrequent among individuals with an actionable genotype. Because the enrolling physicians used alternative strategies to mitigate adverse drug effects—prescribing simvastatin doses lower than 80 mg to avoid myopathy [ 44 ], warfarin titration based on INR [ 45 ], and concurrent prescription of proton pump inhibitors for patients treated with NSAIDs [ 46 ]––only three patients received genotype-directed medication adjustments. Several patients with variant genotypes were not recommended by the precision medicine team to undergo genotype-directed drug adjustments in the event they were stable on a long-term prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Oral anticoagulants, including warfarin and novel oral anticoagulants (NOACs), are used to treat venous thromboembolism, such as pulmonary embolism and deep vein thrombosis, and prevent stroke in patients with atrial fibrillation ( Keeling et al, 2011 ; Mueck et al, 2014 ; Cohen et al, 2015 ; Cohen et al, 2016 ; Witt et al, 2016 ; Bai et al, 2017 ). If used improperly, oral anticoagulants can result in thrombosis or bleeding ( Lin et al, 2019 ; Shields et al, 2019 ) and therefore reduce the quality of life ( Lozano Sanchez and Areitio-Aurtena Bolumburu, 2008 ; Sallinen et al, 2019 ). Dissatisfaction with anticoagulation is associated with poor adherence, international normalized ratio (INR) control, and clinical outcomes ( Perino et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%